Advanced Endoscopic Imaging and Interventions in GERD: An Update and Future Directions - Mann, Rupinder; Gajendran, Mahesh; Perisetti, Abhilash; Goyal, Hemant; Saligram, Shreyas; Umapathy, Chandraprakash (Frontiers in Medicine, 2021)
Gastroesophageal reflux disease (GERD) is one of the most common gastrointestinal diseases encountered in primary care and gastroenterology clinics. Most cases of GERD can be diagnosed based on clinical presentation and risk factors; however, some patients present with atypical symptoms, which can make diagnosis difficult. An esophagogastroduodenoscopy can be used to assist in diagnosis of GERD, though only half of these patients have visible endoscopic findings on standard white light endoscopy. However, the early complications of GERD may be hard to detect with standard white light endoscopy. This led to the development of new advanced endoscopic imaging techniques that is used to detect complications associated with GERD like Barrett's esophagus, and early esophageal adenocarcinoma. Treatment of GERD is important to prevent complications. Management of GERD includes lifestyle modifications, pharmacological therapy, endoscopic and surgical intervention. Minimally invasive endoscopic intervention can be an option in selected patients and without complications of GERD. These endoscopic interventions include endoscopic fundoplication, endoscopic mucosal resection techniques, ablative techniques, creating mechanical barriers, and suturing and stapling devices. As these new advanced endoscopic techniques are emerging, data surrounding the indications, advantages and disadvantages of these techniques need a thorough understanding.